Hypocalcemic tetany in a pet lamb fed with cow milk - GIADINIS (Ν.Δ. ΓΙΑΔΙΝΗΣ), N. D.; ABD EL-TAWAB, M. M.; POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S.; ARGIROUDIS (Σ. ΑΡΓΥΡΟΥΔΗΣ), S.; KARATZIAS (X. ΚΑΡΑΤΖΙΑΣ), H. (Journal of the Hellenic Veterinary Medical Society, 2018)
A 30-days old pet lamb, that was fed with cow milk and pieces of bread was admitted to the Clinic of Farm Animals, because on the same morning it was found inappetent and depressed. A few minutes after admission it developed muscular tremors and convulsions. On clinicopathological evaluation serum calcium concentration was lower than normal. Treatment with calcium borogluconate was very effective in alleviating the signs. Hypocalcemic tetany can occur in young lambs fed with cow milk.